PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGANKOMPETENSI KOMUNIKASI DAN MOTIVASI SEBAGAI PEMEDIASI - Vito Nugraha Soerosemito; Muhammad Cholil (CAPITAL: Jurnal Ekonomi dan Manajemen, 2018)
This study aimed to analyze the influence and leadership relations, communication competence, motivation on organizational citizenship behavior (OCB) employee PDAM Surakarta. The sample in this study amounted to 80 respondents and they are employees of the production, accounting and transmission. Collecting data using direct survey method with questionnaire instrument. Test hypotheses using regression analysis with a significance level of 0.05. Test mediating variables using Baron and Kenny. The results of this research showed that the relationship between transformational leadership and OCB showed that communication competence and motivation mediate its full effect between the leadership of the OCB employee.Keywords: Leadership, Communication, communicative competence, motivation, organizational citizenship behavior, OCB